Juridical Analysis Of The Binding Strength Of A Power Of Power To Charge Lien Rights In The Payable And Receivable Agreement - Irman Pasaribu; Soerya Respationo; Erniyanti Erniyanti; Markus Gunawan (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2024)
The research entitled Juridical Analysis of the Sale and Purchase of Plots of Land That Have Not Been Certified in Kampung Tengah Nongsa, Batam City, the problem is How is the Legal Regulation of the Sale and Purchase of Land Plots that have not been certified, How is the Implementation of the Sale and Purchase of Plots of Land that have not been certified and What are the factors that become obstacles to the practice of buying and selling land plots that have not been certified in Kampung Tengah Nongsa, Batam City. This research method uses empirical legal research methods using qualitative techniques and the approach used in this research is a statutory approach and a conceptual approach. To obtain primary data, this was done by means of in-depth interviews (depth interviews). From the research results, it is known that the legal regulations governing the practice of buying and selling land that has not been certified are contained in the Civil Code in articles 1457 and 1458. Apart from that, there are also regulations for buying and selling land according to Customary Law, Government Regulation Number 24 of 1997 concerning Registration Land, Land Management Rights by the Batam Authority as regulated in Presidential Decree Number 41 of 1973 concerning the Batam Island Industrial Area and Arrangements for Transfer of Land Rights and Permits for Transfer of Land Rights as regulated in the Regulation of the Head of the Batam Free Trade Zone and Free Port Concession Agency Number 27 of 2017 concerning Implementation of Land Allocation. The factor that is an obstacle in the practice of buying and selling plots of land that have not been certified in Kampung Tengah Nongsa, Batam City is that the community believes that the Plot Certificate and Land Sale and Purchase Agreement in the form of a Grant Letter are proof of legal ownership and are guaranteed by law, so that sometim